Covalent bond reinforced and toughened graphene oxide composite film as well as preparation method and application thereof
By introducing sulfosuccinic acid into the graphene oxide film for covalent bond crosslinking, the problems of poor stability, insufficient mechanical properties and limited solar water evaporation efficiency in the water environment are solved, and the film's strength, toughness and water evaporation efficiency are significantly improved.
Patent Information
- Application Number
- CN202411719303.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing graphene oxide films have poor stability, insufficient mechanical properties and limited solar water evaporation efficiency in water environments.
By introducing sulfosuccinic acid (SSA) and graphene oxide for covalent bond cross-linking modification, the carboxyl groups in SSA molecules and the hydroxyl groups on GO nanosheets are induced to esterify the carboxylate groups in SSA molecules and the hydroxyl groups on GO nanosheets to form C-O-C covalent bonds, and a cross-linking network with high binding strength is constructed.
It significantly improves the strength, toughness and in-water stability of the film, improves the photothermal conversion performance and water evaporation efficiency, making the GO-SSA graphene oxide composite film outstanding in the field of solar water evaporation.
Smart Images

Figure CN119503787A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the design and optimization of a graphene oxide composite film, in particular to a covalent bond-reinforced and toughened graphene oxide composite film, a preparation method and application thereof in the field of solar water evaporation, and belongs to the technical field of preparation of inorganic nanocomposite materials. Background Art
[0002] Graphene oxide (GO), as a two-dimensional material, has attracted much attention in the field of materials science due to its unique physical and chemical properties and microscopic layered structure. The existing technology uses vacuum filtration to form a layered interlocking structure of single graphene oxide nanosheets at the micrometer scale, thereby assembling into a self-supporting GO membrane. The obtained GO membrane is similar to paper, has excellent flexibility and rigidity, and its strength is better than other similar membrane materials. Unlike polymer membranes, GO membranes have a multi-level layered structure of micro-nano, which can form two-dimensional nanochannels in the horizontal direction and have staggered pores in the vertical direction, which can enable water molecules to be tortuously transmitted between GO nanosheet layers, thereby giving the GO membrane excellent water permeability. The layered "channels" formed inside are nanoscale (about 0.8 nm) and have excellent selective permeability. Micron-level molecules cannot pass through, and only small molecules such as water are allowed to pass freely. This special layered membrane structure makes the material widely used in oil and water separation, water treatment and solar water evaporation.
[0003] However, although GO membranes have shown great application potential in many fields, there are still several technical problems that need to be solved in their actual use. First, the interlayer bonding force of GO membranes mainly depends on van der Waals forces and partial π-π stacking effects, and their bonding strength is relatively low. Since GO membranes have abundant hydrophilic carboxyl and hydroxyl functional groups, when water molecules enter the interlayer, they can easily form hydrogen bonds with these functional groups. As water molecules continue to penetrate, the interlayer spacing increases, and the π-π effect between graphene nanosheets gradually weakens, making the GO membrane less and less stable during contact with water. This defect seriously limits the practicality of GO membranes in water environment-related applications.
[0004] Secondly, there is limited room for optimization of the mechanical properties of GO membranes. Although its strength and toughness are better than those of traditional polymer membranes, it is still difficult to meet the requirements of some engineering application scenarios with high strength and high toughness. Existing studies have attempted to improve the mechanical properties of GO membranes by methods such as composite with polymers, ionic bond modification or hydrogen bond enhancement, but these modification methods have limitations to varying degrees. For example, the binding force of ionic and hydrogen bond modifications is weak and cannot significantly improve the mechanical properties of GO membranes; and the strategy of modifying GO membranes through π-π stacking often faces problems of poor uniformity and low modification efficiency due to the structural characteristics of the modified molecules.
[0005] In addition, there is room for optimization in the performance of GO membranes in terms of photothermal conversion efficiency and water evaporation rate. GO is widely used in the field of solar water evaporation due to its black light absorption characteristics and certain photothermal conversion capabilities. However, pure GO membranes are prone to degradation of photothermal performance due to swelling during long-term use, and their water evaporation efficiency is difficult to meet the needs of high-performance water treatment and evaporation devices. In existing studies, some GO membranes that have achieved performance optimization through surface modification or doping, while improving the evaporation rate, are often limited in their large-scale application due to complex preparation processes and high costs.
[0006] In summary, the existing graphene oxide membranes still have significant deficiencies in terms of stability, mechanical properties, and solar water evaporation efficiency in water environments. These defects limit the scope of use of GO membranes in practical applications. Therefore, how to further improve the stability, mechanical properties, and photothermal properties of graphene oxide membranes in water to meet the needs of different fields is a technical problem that needs to be solved urgently. Summary of the invention
[0007] 1. Problems Solved by the Technology of the Present Invention In view of the defects and shortcomings of the existing graphene oxide film (Graphene Oxide, GO) in water environment, such as poor stability, insufficient mechanical properties and limited solar water evaporation efficiency, in order to overcome at least one of the above and other technical problems in the prior art, the present invention aims to provide a covalent bond reinforced and toughened graphene oxide composite film, a preparation method and its application, by introducing sulfosuccinic acid (SSA) and graphene oxide for covalent cross-linking modification, using acidic conditions and heating to induce the carboxyl groups in the SSA molecules and the hydroxyl groups on the GO nanosheets to undergo esterification reaction and form COC covalent bonds, thereby constructing a cross-linked network with high bonding strength between the GO nanosheets, significantly improving the strength, toughness and stability of the film in water. At the same time, the hydrophilic sulfonic acid group in SSA can improve the water absorption efficiency of the membrane, effectively enhance the photothermal conversion performance and water evaporation efficiency. The GO composite membrane prepared by the present invention not only has significantly improved mechanical properties, but also has excellent solar water evaporation performance, and has broad application prospects.
[0008] (II) Technical solution of the present invention The first invention object of the present invention is to provide a method for preparing a covalent bond-reinforced and toughened graphene oxide composite film, wherein a layered graphene oxide composite film is prepared by a vacuum filtration-induced self-assembly method, and the film is acidified by dripping hydrochloric acid and placed in an oven for heating, so as to achieve covalent cross-linking inside the GO nanosheets, and a series of covalent bond-reinforced and toughened GO-SSA graphene oxide composite films with different proportions are obtained by changing the amount of SSA added, and the implementation steps are as follows: SS1. Preparation of GO aqueous dispersion Prepare a monolayer graphene oxide (GO) aqueous dispersion to ensure that the GO nanosheet monolayer rate is not less than 99.5%, the average radial size is 20-30 μm, and the GO concentration is controlled at 0.8-1.2 mg / mL to provide a nanosheet base material with uniform dispersion; SS2. Prepare sulfosuccinic acid (SSA) solution and mix Weigh 100-400 mg of 65-75 wt% sulfosuccinic acid (SSA) using a balance and add it dropwise to the aqueous dispersion of graphene oxide (GO). The mass ratio of GO to SSA is controlled at 1:5 to 1:20. Stir the mixed solution for 5-8 hours to fully mix SSA and GO to obtain a mixed solution of GO and SSA. SS3. Ultrasonic dispersion Using water bath ultrasound, the mixed solution of GO and SSA prepared in step SS2 is placed in an ultrasonic water bath with a power of 90–110 W for ultrasonic dispersion for 5–10 min, and the ultrasonic temperature is controlled not to be higher than 25°C to fully disperse the GO nanosheets and ensure the formation of a uniform nanoscale suspension; SS4. Vacuum filtration induced membrane assembly The mixed solution of GO and SSA after ultrasonic dispersion in step SS3 is vacuum filtered through a water-based microporous filter membrane with a pore size of 0.4-0.5 μm, and the vacuum degree of the filtration is not less than 0.08 MPa, so as to induce GO and SSA to self-assemble into a thin film with a micro-nano multi-level layered structure until a preliminary self-assembled film is formed; SS5. Acidification After all the water is drained, continue to drop 0.5-1mL of 4-6 mol / L hydrochloric acid into the film preliminarily self-assembled on the water-based microporous filter membrane in step SS4, and continue vacuum filtration until the acidified liquid is completely drained to obtain the acidified self-assembled film, and ensure that the hydroxyl groups on the surface of the GO nanosheets are fully exposed and can participate in subsequent chemical reactions; SS6. Heat treatment cross-linking The acidified self-assembled film obtained in step SS5 is placed in a vacuum drying oven for heat treatment for 1-3 hours, and the temperature is adjusted to 70-90 °C and the pressure is 0.8-1.2 atmospheres, so that GO and SSA undergo a covalent cross-linking reaction, and a COC covalent bond is formed by the esterification reaction of the SSA carboxyl group and the GO hydroxyl group to construct an interlayer cross-linking network with high bonding strength, and finally a covalently reinforced and toughened GO-SSA graphene oxide composite film is obtained; SS7. Performance Optimization The mass of SSA weighed in step SS2 was adjusted and mixed with the GO aqueous solution with the same content, and steps SS3 to SS6 were repeated to obtain a series of GO-SSA graphene oxide composite membranes with different SSA contents and different mechanical properties and photothermal properties. The covalently bond-reinforced and toughened graphene oxide composite membranes with the best mechanical strength and toughness were screened out, the best performance ratio was determined, and the thickness of the obtained composite membrane with the best performance was controlled within the range of 3-5 μm, the tensile strength reached 400-420 MPa, and the toughness reached 10-12 MJ / m 3 , the water evaporation rate reaches 2.0 kg·m -2 ·h -1 above.
[0009] The second inventive object of the present invention is to provide a covalent bond reinforced and toughened graphene oxide composite film, the preparation of which is based on the above-mentioned covalent bond reinforced and toughened graphene oxide composite film preparation method.
[0010] The third inventive object of the present invention is to provide an application of the above-mentioned covalent bond reinforced and toughened graphene oxide composite film as a substrate material in a solar water evaporation device.
[0011] Working principle of the present invention: The components of many organisms in nature (such as bones, tendons, abalone shell pearl layers, etc.) have excellent mechanical properties, which is due to the exquisite multi-level structure and rich interface effects of the component materials. Therefore, the preparation of inorganic nanomaterials with micro-nano multi-level regular orientation and modification with strong interface effects is the key to improving the macroscopic mechanical properties of inorganic nanomaterials. The present invention introduces sulfosuccinic acid (SSA) and uses hydrophilic organic small molecules SSA to covalently cross-link the GO nanosheets. The obtained GO-SSA composite membrane has a micro-nano multi-level layered structure, and a covalent bond cross-linking network is formed between the GO nanosheets, so that the strength and toughness of the GO-SSA graphene oxide composite membrane are significantly improved compared with before modification. At the same time, the sulfonic acid group on the SSA molecular chain has extremely strong hydrophilicity, which can improve the water absorption capacity of the composite membrane and enhance its water evaporation efficiency in solar water evaporation. In addition, the two-dimensional nanochannels and staggered pore structure of the GO nanosheets give the membrane excellent water molecule selective permeability. The uniform distribution of SSA effectively suppressed the defect of pure GO membrane that is easy to swell in water and significantly improved the stability of the composite membrane in a humid environment.
[0012] (III) Technical Effects of the Invention Compared with the existing technology for preparing graphene oxide composite films, the covalent bond reinforced and toughened graphene oxide composite film, preparation method and application of the present invention have the following characteristics and advantages: (1) Using an organic small molecule SSA with carboxyl groups at both ends of the molecular chain and containing hydrophilic sulfonic acid groups as a crosslinker, it undergoes an esterification reaction with the hydroxyl groups on the GO nanosheets under acidic conditions and a certain temperature, so that SSA covalently crosslinks the interlayers of the GO nanosheets to form a nano-toughened structure, thereby obtaining a covalently reinforced and toughened GO-SSA graphene oxide composite film. The prepared GO-SSA graphene oxide composite film has a maximum strength of 419 MPa and a toughness of 11 MJ / m 3 , purer GO membrane (strength 126 MPa, toughness 2.6 MJ / m 3 ) have been greatly improved.
[0013] (2) The present invention significantly improves the stability of the GO membrane in water through covalent cross-linking, and solves the problem that the pure GO membrane is easy to swell in a humid environment. The pure GO membrane has abundant hydrophilic carboxyl and hydroxyl functional groups, and can form two-dimensional nanochannels in the horizontal direction, and has a staggered pore structure in the vertical direction, which can allow water molecules to pass through. The GO membrane itself is black and has a certain light-to-heat conversion ability. Therefore, the material can be used in solar water evaporation devices. However, the pure GO membrane is easy to swell in water and is unstable. In the covalently cross-linked graphene oxide composite membrane prepared by the present invention, some oxygen-containing functional groups between GO layers are covalently cross-linked, which improves the stability of the graphene oxide composite membrane in water. In addition, the GO-SSA graphene oxide composite membrane has hydrophilic sulfonic acid groups, which helps to improve the water absorption efficiency of the membrane.
[0014] (3) The GO-SSA composite film of the present invention has excellent performance in solar water evaporation, with significant improvement in photothermal conversion efficiency and water evaporation rate. The water evaporation rate of pure graphene oxide film under 1 sun intensity reaches 1.65 kg·m -2 ·h -1 The GO-SSA graphene oxide composite membrane of the present invention can increase the water evaporation rate to a maximum of 2.11 kg·m -2 ·h -1 This technical effect makes the material potentially widely used in the field of solar water evaporation, such as solar seawater desalination and water resource recovery.
[0015] (4) The preparation method adopted by the present invention is simple and controllable. The performance of the composite membrane can be precisely controlled by adjusting the ratio of GO to SSA. The entire preparation process is carried out under mild conditions, without the need for complex instruments and equipment and harsh reaction conditions, and has good prospects for industrial application. In addition, the raw materials used are widely available and low in cost, which further enhances the practical value of the technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1The present invention is a flow chart for preparing a covalent bond-reinforced and toughened graphene oxide composite film; Figure 2 A schematic diagram of the preparation of a covalent bond-reinforced and toughened graphene oxide composite film according to the present invention; Figure 3 The microstructure and sulfur element analysis diagram of the GO-SSA graphene oxide composite film, wherein Figure A is a scanning electron microscope photo of the cross-sectional structure of the GO-SSA graphene oxide composite film, Figure B is a sulfur element distribution diagram of the corresponding area of Figure A, and Figure C is a sulfur element spectrum in the X-ray photoelectron spectroscopy analysis (XPS) of the GO-SSA graphene oxide composite film; Figure 4 Figure 1 is a spectrum characterization diagram, wherein Figure A is the infrared spectrum of GO film and GO-SSA graphene oxide composite film; Figure B is the X-ray diffraction spectrum of GO film and GO-SSA graphene oxide composite film; Figure C is the X-ray photoelectron spectrum of GO film; Figure D is the X-ray photoelectron spectrum of GO-SSA graphene oxide composite film; Figure 5 Figure 1 is a comparison of the mechanical properties of GO-SSA graphene oxide composite membranes, wherein Figure A is a stress-strain curve of GO membranes and GO-SSA graphene oxide composite membranes; Figure B is a performance comparison of the strength and toughness of GO-SSA graphene oxide composite membranes and GO composite films modified by other methods; Figure 6 The solar water evaporation performance curves of GO membrane and GO-SSA graphene oxide composite membrane, wherein Figure A shows the temperature rise data of pure water, GO membrane and GO-SSA graphene oxide composite membrane under 1 sun intensity; Figure B shows the water loss weight data of pure water, GO membrane and GO-SSA graphene oxide composite membrane under 1 sun intensity. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical scheme and advantages of the implementation of the present invention clearer, the technical scheme in the embodiment of the present invention will be described in more detail below in conjunction with the drawings in the embodiment of the present invention. The described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The embodiments described below with reference to the drawings are exemplary and are intended to be used to explain the present invention, and should not be understood as limiting the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] The present invention aims to provide a covalently bond-reinforced and toughened graphene oxide composite membrane, a preparation method and its application, by introducing sulfosuccinic acid (SSA) and graphene oxide for covalent cross-linking modification, using acidic conditions and heating to induce the carboxyl groups in the SSA molecules to react with the hydroxyl groups on the GO nanosheets to undergo esterification and form COC covalent bonds, thereby constructing a cross-linked network with high bonding strength between the GO nanosheets, significantly improving the strength, toughness and stability of the membrane in water. At the same time, the hydrophilic sulfonic acid group in SSA can improve the water absorption efficiency of the membrane, effectively enhancing the photothermal conversion performance and water evaporation efficiency.
[0019] Example 1 like Figure 1 , 2 As shown, the method for preparing the covalent bond-reinforced and toughened graphene oxide composite film of the present invention mainly comprises the following steps when implemented: SS1. Preparation of GO aqueous dispersion: Prepare an aqueous dispersion of monolayer graphene oxide to ensure that the monolayer rate of GO nanosheets is not less than 99.5%, the average radial size is 20–30 μm, and the GO concentration is controlled at 0.8–1.2 mg / mL to provide a nanosheet base material with uniform dispersion.
[0020] SS2. Prepare sulfosuccinic acid (SSA) solution and mix: First, use a balance to weigh a series of 70 wt% SSA aqueous solutions and add them to the prepared GO aqueous solution, stirring to mix. The mass ratios of GO and SSA are 1:5, 1:10, 1:15, and 1:20, respectively. Stir the mixed solution for 5–8 hours to fully mix SSA and GO to obtain a mixed solution of the two.
[0021] SS3. Ultrasonic dispersion: Use water bath ultrasound to place the mixed solution of GO and SSA prepared in step SS2 in an ultrasonic water bath with a power of 90–110 W for ultrasonic dispersion for 5–10 min. Control the ultrasonic temperature to be no higher than 25°C to fully disperse the GO nanosheets and ensure the formation of a uniform nanoscale suspension.
[0022] SS4. Vacuum filtration induced film assembly: The mixed solution of GO and SSA after ultrasonic dispersion was poured into a filtration bottle, and a layered film was prepared by vacuum filtration induced self-assembly. Specifically, the mixed solution was vacuum filtered through a water-based microporous filter membrane with a pore size of 0.4-0.5 μm. The filtration vacuum degree was not less than 0.08 MPa, inducing GO and SSA to self-assemble into a film with a micro-nano multi-level layered structure until a preliminary self-assembled film was formed.
[0023] SS5. Acidification: After all the water is drained, add 0.5–1 mL of 4–6 mol / L hydrochloric acid to the filtered membrane, and then continue to filter until the liquid is completely drained to acidify the membrane and obtain the acidified self-assembled membrane to ensure that the hydroxyl groups on the surface of the GO nanosheets are fully exposed and can participate in subsequent chemical reactions.
[0024] SS6. Heat treatment cross-linking: Place the filtered membrane in a vacuum drying oven and heat for 1-3 hours, adjust the temperature to 70-90 °C, and the pressure to 0.8-1.2 atmospheres. During this process, GO and SSA undergo covalent cross-linking reaction, and the esterification reaction of SSA carboxyl groups and GO hydroxyl groups forms COC to form covalent bonds to construct an interlayer cross-linked network with high bonding strength, thereby finally obtaining GO-SSA graphene oxide composite membranes with different degrees of covalent cross-linking.
[0025] SS7. Performance optimization: Adjust the mass of SSA weighed in step SS2, blend it with the same content of GO aqueous solution, repeat steps SS3 to SS6, and obtain a series of GO-SSA graphene oxide composite membranes with different SSA contents and different mechanical properties and photothermal properties. Select the covalently bond-reinforced and toughened graphene oxide composite membranes with the best mechanical strength and toughness, determine the best performance ratio, and ensure that the thickness of the composite membrane with the best performance is controlled in the range of 3-5μm, the tensile strength reaches 400-420MPa, and the toughness reaches 10-12MJ / m 3 , the water evaporation rate reaches 2.0 kg·m -2 ·h -1 above.
[0026] Preferably, in each of the above steps, the GO aqueous solution is a graphene oxide aqueous dispersion having a monolayer rate of>99.5%, an average radial size of 20-30 um, and a surface containing active groups such as carboxyl, epoxy, and hydroxyl groups, and a film having a microscopic layered structure can be prepared by vacuum filtration; the SSA is an SSA aqueous solution with a mass fraction of 70 wt%; the covalent crosslinking of the GO and SSA is that under acidic and heating conditions, the hydroxyl groups on the GO surface can undergo an esterification reaction with the carboxyl groups on the small molecule SSA, and the formed COC covalent bonds cause the GO nanosheets to form interlayer covalent crosslinking, thereby improving the strength and toughness of the GO-SSA graphene oxide composite film. Since the small molecule SSA molecular chain carries a hydrophilic sulfonic acid group, the hydrophilicity of the GO-SSA graphene oxide composite film is simultaneously improved, and the solar water evaporation efficiency of the GO-SSA graphene oxide composite film is significantly improved. The thickness range of the GO-SSA graphene oxide composite film obtained by the present invention is 3-5 microns.
[0027] Preferably, in the above step SS1, the preparation process of the GO aqueous dispersion comprises: dispersing graphite oxide powder in deionized water at a concentration of 0.8-1.2 mg / mL, performing ultrasonic exfoliation for 60-90 min using a probe-type ultrasonic device with a power of 400-600 W, controlling the temperature not to exceed 15 ° C using an ice water bath during the ultrasonic process, then centrifuging at a speed of 4000-6000 rpm for 10-20 min, and collecting the supernatant to obtain a GO aqueous dispersion with a monolayer rate of not less than 99.5%.
[0028] Preferably, in the above step SS2, the mixing process of GO and SSA further comprises: using a magnetic stirrer during the stirring process, controlling the rotation speed to 300-500 rpm, maintaining the stirring temperature at 20-25°C, sampling every 2 hours to test the dispersion stability of the mixed solution by dynamic light scattering method to ensure the dispersion uniformity of the GO nanosheets, until the measured particle size distribution curve remains stable.
[0029] Preferably, in the above step SS3, the temperature range of the ultrasonic water bath is controlled at 20-25 °C, and the ultrasonic process adopts an intermittent ultrasonic method, that is, working for 2 minutes and then pausing for 1 minute, and the cycle is repeated 3-5 times. At the same time, a thermometer is used to monitor the solution temperature in real time. When the temperature exceeds 25 °C, the ultrasound is stopped immediately, and the process is continued when the temperature drops below 20 °C, so as to further reduce the probability of particle sedimentation and enhance the dispersion effect of the mixed solution, thereby improving the microstructure uniformity and film formation quality of the subsequent film layer.
[0030] Preferably, in the above step SS4, the method of inducing self-assembly film formation by vacuum filtration method comprises at least the following sub-steps: SS41. Solution pretreatment: The mixed solution of GO and SSA obtained by ultrasonic dispersion in step SS3 is allowed to stand for 2–5 min to ensure the uniformity of the solution and avoid the uniform film formation effect due to particle aggregation or sedimentation; SS42. Initial filtration operation: When the vacuum pump is not turned on, add the GO and SSA mixed solution after standing to the vacuum filtration device to ensure that the mixed solution evenly covers the surface of the filter membrane; SS43. Start vacuum filtration: Keep the mixed solution of GO and SSA in the vacuum filtration device for 2–5 min to ensure that the GO and SSA molecules are fully in contact with the filter membrane, then gradually start the vacuum pump for vacuum filtration, control the vacuum degree between 0.08–0.10 MPa, and ensure that the filtration speed is slow and uniform to avoid defects or damage on the membrane surface due to liquid flow impact; SS44. Micro-control of membrane layer: During the filtration process, GO nanosheets in the mixed solution of GO and SSA gradually deposit on the filter membrane to form a layered microstructure, while SSA small molecules are distributed between the GO nanosheets and deposited on the filter membrane together. By adjusting the filtrate discharge rate in real time, the deposition rate and distribution of GO and SSA on the filter membrane surface are optimized to ensure that the final membrane has a good micro-nano multi-level layered structure. SS45. Complete filtration and drying: The filtration operation continues until the water is completely drained and a uniform and dense graphene oxide composite membrane mixed with SSA is formed on the surface of the filter membrane. After stopping the vacuum pump, the filter membrane is taken out and placed in ventilation conditions for natural air drying or in a dry environment at a temperature of 25-35°C for 30-60 minutes to remove residual moisture and avoid high temperature causing unstable membrane morphology or loose structure.
[0031] Preferably, in the above step SS5, the hydrochloric acid is added in a stepwise manner, and the amount of each addition is controlled to be 20-30% of the total amount to ensure that the acid solution is evenly distributed on the surface of the film, and vacuum filtration is performed after each addition to ensure that the acidification process is uniform and sufficient to avoid local insufficient acidification or over-acidification that affects the exposure effect of the hydroxyl groups of the GO nanosheets; and during the acidification process, 0.5-1 wt% ethanol or isopropanol is added to the hydrochloric acid solution as an auxiliary agent to improve the acidification efficiency and slow down the shrinkage of the membrane structure to maintain the uniformity and integrity of the membrane layer after acidification, thereby providing a better structural basis for subsequent cross-linking.
[0032] Preferably, in the above step SS6, the heat treatment cross-linking process also includes: controlling the pressure of the vacuum drying oven at 0.8-1.2 atmospheres, and increasing the temperature gradient during the heating process so that the initial temperature is 50-60 °C and gradually increases to 70-90 °C to avoid deformation or stratification of the membrane layer due to rapid temperature rise, while ensuring that the esterification reaction is fully carried out. After the temperature reaches 70-90 °C, it is treated at a constant temperature for 2 hours, and then naturally cooled to room temperature at a cooling rate of 1 °C / min. The entire heat treatment process is carried out under nitrogen protection, and the nitrogen flow rate is controlled at 100-150 mL / min, so that the stability of the membrane structure is further enhanced, the mechanical properties and water stability of the GO-SSA composite membrane are improved, and the long-term use effect of the finished membrane in complex environments is ensured.
[0033] Preferably, in the above step SS7, SSA is modified by adding polyhydroxy compounds (such as glycerol, sorbitol) or amino compounds (such as ethylenediamine, triethanolamine) as functional group modifiers, so that it forms a more stable covalent cross-linked network with GO nanosheets during acidification and heat treatment, and by optimizing the mass ratio of GO to SSA to 1:10 to 1:25, the thickness and interlayer structure of the film layer are systematically regulated to further improve the photothermal conversion efficiency of the composite film at an intensity of 1 sun, thereby screening out a GO-SSA composite film with higher photothermal conversion efficiency.
[0034] Example 2 As a more specific example, when implementing Example 2: First, dilute the graphene oxide dispersion into a GO dispersion with a concentration of 1 mg / mL, and take 20 mL for standby. Weigh 100 mg of SSA aqueous solution with a mass fraction of 70 wt% and add it dropwise to the prepared 20 mLGO dispersion. During the dropwise addition, the GO dispersion is kept in a state of continuous mechanical stirring, and the dropwise addition is continued for about 10 hours. Then, use an ultrasonic water bath with a power of 100 w, the ultrasonic temperature is not higher than 25 ° C, and the ultrasonic is 10 min to fully disperse the GO nanosheets. At this time, the solution is brown and translucent. Pour the mixed solution into a suction flask for vacuum filtration, and the filter membrane used is a water filter membrane with a pore size of 0.45 μm. After the liquid is drained, a black opaque film is deposited on the filter membrane. Stop the filtration device, unplug the suction tube, continue to drip hydrochloric acid with a concentration of 5 mol / L into the suction flask, and continue to vacuum filter until it is drained to fully acidify the membrane. After the liquid was drained again, the filter membrane was removed and placed in an oven with the oven temperature set to 80 °C. During the oven heating process, the black film gradually separated from the filter membrane to form an independent film. This heating process took about 1 hour. When the temperature rose to 80 °C, the acidified GO nanosheets and SSA began to undergo esterification reaction. This process took about 1 hour to obtain a covalently cross-linked GO-SSA graphene oxide composite membrane. The obtained GO-SSA graphene oxide composite membrane was characterized by infrared spectroscopy and found that after this reaction time, at ~ 1032 cm -1 Thereafter, the characteristic peak appears at . After that, prolonging the time of placing the film in the oven will not change the characteristic peak here, indicating that the reaction conditions and time can fully react the hydroxyl groups on the GO nanosheets with the carboxyl groups on the SSA. The parallel samples of the GO-SSA graphene oxide composite film obtained by this method have an average tensile strength of 159 MPa and an average toughness of 3.7 MJ / m 3 .
[0035] Example 3 As another preferred example, when implementing this embodiment 3: dilute the graphene oxide dispersion into a GO dispersion with a concentration of 1 mg / mL, and take 20 mL for standby. Weigh 200 mg of a 70 wt% SSA aqueous solution and add it dropwise to the prepared 20 mL GO dispersion. During the addition, the GO dispersion is kept in a state of continuous mechanical stirring, and the addition is continued for about 10 hours. Then, an ultrasonic water bath with a power of 100 w is used, and the ultrasonic temperature is not higher than 25 ° C. The ultrasonic wave is ultrasonicated for 10 minutes to fully disperse the GO nanosheets, and the solution is brown and translucent. The mixed solution is poured into a suction flask for vacuum filtration, and the filter membrane used is a water filter membrane with a pore size of 0.45 μm. After the liquid is drained, a black opaque film is deposited on the filter membrane. Stop the filtration device, unplug the filtration tube, continue to drip hydrochloric acid with a concentration of 5 mol / L into the filtration flask, and continue to vacuum filter until it is drained to fully acidify the membrane. After the liquid was drained again, the filter membrane was removed and placed in an oven with the oven temperature set to 80 °C. During the oven heating process, the black film gradually separated from the filter membrane to form an independent film. This heating process took about 1 hour. When the temperature rose to 80 °C, the acidified GO nanosheets and SSA began to undergo esterification reaction. This process took about 1 hour to obtain a covalently cross-linked GO-SSA graphene oxide composite membrane. The obtained GO-SSA graphene oxide composite membrane was characterized by infrared spectroscopy and found that after this reaction time, at ~ 1032 cm -1 Thereafter, the characteristic peak appears at . After that, prolonging the time of placing the film in the oven will not change the characteristic peak here, indicating that the reaction conditions and time can fully react the hydroxyl groups on the GO nanosheets with the carboxyl groups on the SSA. The parallel samples of the GO-SSA graphene oxide composite film obtained by this method have an average tensile strength of 251 MPa and an average toughness of 7.4 MJ / m 3 .
[0036] Example 4 As another preferred example, when implementing this embodiment 4: dilute the graphene oxide dispersion into a GO dispersion with a concentration of 1 mg / mL, and take 20 mL for standby. Weigh 300 mg of a 70 wt% SSA aqueous solution and add it dropwise to the prepared 20 mL GO dispersion. During the addition, the GO dispersion is kept in a state of continuous mechanical stirring, and the addition is continued for about 10 hours. Then, an ultrasonic water bath with a power of 100 w is used, and the ultrasonic temperature is not higher than 25 ° C. The ultrasonic wave is ultrasonicated for 10 minutes to fully disperse the GO nanosheets, and the solution is brown and translucent. The mixed solution is poured into a suction flask for vacuum filtration, and the filter membrane used is a water filter membrane with a pore size of 0.45 μm. After the liquid is drained, a black opaque film is deposited on the filter membrane. Stop the filtration device, unplug the filtration tube, continue to drip hydrochloric acid with a concentration of 5 mol / L into the filtration flask, and continue to vacuum filter until it is drained to fully acidify the membrane. After the liquid was drained again, the filter membrane was removed and placed in an oven with the oven temperature set to 80 °C. During the oven heating process, the black film gradually separated from the filter membrane to form an independent film. This heating process took about 1 hour. When the temperature rose to 80 °C, the acidified GO nanosheets and SSA began to undergo esterification reaction. This process took about 1 hour to obtain a covalently cross-linked GO-SSA graphene oxide composite membrane. The obtained GO-SSA graphene oxide composite membrane was characterized by infrared spectroscopy and found that after this reaction time, at ~ 1032 cm -1 Thereafter, the characteristic peak appears at . After that, prolonging the time of placing the film in the oven will not change the characteristic peak here, indicating that the reaction conditions and time can fully react the hydroxyl groups on the GO nanosheets with the carboxyl groups on the SSA. The parallel samples of the GO-SSA graphene oxide composite film obtained by this method have an average tensile strength of 419 MPa and an average toughness of 11 MJ / m 3 .
[0037] Example 5 As another preferred example, when implementing this embodiment 5: dilute the graphene oxide dispersion into a GO dispersion with a concentration of 1 mg / mL, and take 20 mL for standby. Weigh 400 mg of a 70 wt% SSA aqueous solution and add it dropwise to the prepared 20 mL GO dispersion. During the addition, the GO dispersion is kept in a state of continuous mechanical stirring, and the stirring is continued for about 10 hours after the addition. Then, use an ultrasonic water bath with a power of 100 w, the ultrasonic temperature is not higher than 25 ° C, and the ultrasonic is 10 minutes to fully disperse the GO nanosheets. At this time, the solution is brown and translucent. Pour the mixed solution into a suction flask for vacuum filtration, and the filter membrane used is a water filter membrane with a pore size of 0.45 μm. After the liquid is drained, a black opaque film is deposited on the filter membrane. Stop the filtration device, unplug the filtration tube, continue to drip hydrochloric acid with a concentration of 5 mol / L into the filtration flask, and continue to vacuum filter until it is drained to fully acidify the membrane. After the liquid was drained again, the filter membrane was removed and placed in an oven with the oven temperature set to 80 °C. During the oven heating process, the black film gradually separated from the filter membrane to form an independent film. This heating process took about 1 hour. When the temperature rose to 80 °C, the acidified GO nanosheets and SSA began to undergo esterification reaction. This process took about 1 hour to obtain a covalently cross-linked GO-SSA graphene oxide composite membrane. The obtained GO-SSA graphene oxide composite membrane was characterized by infrared spectroscopy and found that after this reaction time, at ~ 1032 cm -1 Thereafter, the characteristic peak appears at . After that, prolonging the time of placing the film in the oven will not change the characteristic peak here, indicating that the reaction conditions and time can fully react the hydroxyl groups on the GO nanosheets with the carboxyl groups on the SSA. The parallel samples of the GO-SSA graphene oxide composite film obtained by this method have an average tensile strength of 162 MPa and an average toughness of 4.2 MJ / m 3 .
[0038] Structure and performance characterization of GO-SSA graphene oxide composite membrane like Figure 2-6 As shown, the structure and properties of the covalent bond reinforced and toughened graphene oxide composite film (GO-SSA composite film) of the present invention have been comprehensively characterized by microscopic analysis and performance testing, demonstrating its excellent mechanical properties, chemical structure characteristics and solar water evaporation performance.
[0039] Figure 2The figure shows the implementation schematic diagram of the preparation of the covalent bond-reinforced and toughened graphene oxide composite membrane (GO-SSA composite membrane) of the present invention: the fully mixed GO and SSA aqueous dispersion are self-assembled into a layered film by vacuum filtration; after the film is fully acidified by hydrochloric acid and heated in an oven, a covalently cross-linked GO-SSA graphene oxide composite membrane is obtained. Among them, the figure shows the interlayer cross-linking structure formed by the small molecule SSA and the GO nanosheet through covalent bonds through the chemical structural formula: the hydroxyl group in the GO nanosheet and the carboxyl group in the SSA in the organic small molecule form a covalent bond through esterification reaction, so that the GO nanosheet interlayer is cross-linked, thereby improving the mechanical properties of the GO-SSA graphene oxide composite membrane.
[0040] Figure 3 Figure 3 is the microstructure and sulfur element analysis diagram of GO-SSA graphene oxide composite membrane. Figure A is a cross-sectional scanning electron microscope photograph of the GO-SSA graphene oxide composite membrane, indicating that the membrane has a microscopic layered structure inside; Figure B shows that a large amount of sulfur is distributed between the layers of the GO-SSA graphene oxide composite membrane, indicating that SSA is evenly distributed between the GO nanosheets; Figure C further shows that SSA enters the GO nanosheet layers through the sulfur element spectrum in the X-ray photoelectron energy spectrum.
[0041] Figure 4 Figure 1 is a spectrum characterization diagram: Figure A is the infrared spectrum of GO membrane and GO-SSA graphene oxide composite membrane. The modified GO-SSA has a wavelength of ~1032 cm -1 A new absorption peak appears at ~1224 cm -1 The CO absorption peak at 288 eV is significantly enhanced, indicating that the number of CO bonds in the GO-SSA graphene oxide composite film is significantly increased compared with the pure GO film, which supplements the formation of COC covalent bonds in the GO-SSA graphene oxide composite film; Figure B is the X-ray diffraction spectrum of the GO film and the GO-SSA graphene oxide composite film. The diffraction peak of the GO-SSA graphene oxide composite film is significantly blue-shifted compared with the pure GO film, indicating that the addition of SSA increases the interlayer spacing of the GO nanosheets, indicating that the SSA in the GO-SSA graphene oxide composite film is inserted into the interlayer of the GO nanosheets; Figure C is the X-ray photoelectron spectrum of the GO film; Figure D is the X-ray photoelectron spectrum of the GO-SSA graphene oxide composite film. Compared with Figure C, the intensity of the CO absorption peak at a peak position of about 288 eV increases significantly, indicating that new CO chemical bonds are generated, further indicating that COC covalent bonds are formed inside the GO-SSA graphene oxide composite film.
[0042] Figure 5The figure is a comparison of the mechanical properties of the GO-SSA composite membrane: Figure A is the stress-strain curves of the GO membrane and a series of GO-SSA graphene oxide composite membranes: 1 is the stress-strain curve of the pure GO membrane, 2 is the stress-strain curve of the GO-SSA graphene oxide composite membrane with a covalent bond reinforced and toughened ratio of GO to SSA of 1:5 by mass percentage, 3 is the stress-strain curve of the GO-SSA graphene oxide composite membrane with a covalent bond reinforced and toughened ratio of GO to SSA of 1:10 by mass percentage, 4 is the stress-strain curve of the GO-SSA graphene oxide composite membrane with a covalent bond reinforced and toughened ratio of GO to SSA of 1:15 by mass percentage, 5 is the stress-strain curve of the GO-SSA graphene oxide composite membrane with a covalent bond reinforced and toughened ratio of GO to SSA of 1:20 by mass percentage. The above data show that the covalent bond-reinforced and toughened GO-SSA graphene oxide composite film with a mass percentage of GO and SSA of 1:15 has the best mechanical properties; Figure B is a performance comparison of the strength and toughness of the GO-SSA graphene oxide composite film and the GO film modified by other methods. The data in the figure show that the GO-SSA graphene oxide composite film has the combined advantages of strength and toughness, and its strength and toughness are about 3 times and 4 times higher than those of the pure GO film, respectively.
[0043] Figure 6 The solar water evaporation performance curves of GO membrane and GO-SSA graphene oxide composite membrane: Figure A shows the temperature rise data of pure water, GO membrane and GO-SSA graphene oxide composite membrane under 1 sun intensity. The results show that GO-SSA graphene oxide composite membrane has the highest temperature rise efficiency; Figure A shows the water evaporation data of pure water, GO membrane and GO-SSA graphene oxide composite membrane under 1 sun intensity; Figure B shows the water loss weight data of pure water, GO membrane and GO-SSA graphene oxide composite membrane under 1 sun intensity. The results show that GO-SSA graphene oxide composite membrane has the highest water evaporation efficiency, which can reach 2.11kg·m -2 ·h -1 .
[0044] In summary, the covalent bond-reinforced and toughened graphene oxide composite membrane GO-SSA composite membrane prepared by the present invention combines the multiple advantages of mechanical properties, chemical stability and photothermal properties. Its covalent cross-linked network significantly enhances the structural stability of the membrane, while the introduction of SSA molecules improves the hydrophilicity and water evaporation efficiency of the composite membrane. The measurement results show that its maximum strength and toughness are respectively increased by about 3 times and 4 times compared with those before modification, and the water evaporation rate is increased to 2.11 kg·m -2 ·h -1 These properties make this material have broad application prospects in the fields of solar water evaporation, seawater desalination and water resource recycling.
[0045] Through the above embodiments, the purpose of the present invention is fully and effectively achieved. Those skilled in the art can understand that the present invention includes but is not limited to the contents described in the drawings and the above specific embodiments. Although the present invention has been described with respect to the most practical and preferred embodiments currently considered, it should be understood that the present invention is not limited to the disclosed embodiments, and any modification that does not deviate from the functional and structural principles of the present invention will be included in the scope of the claims.
Claims
1. A method for preparing a covalent bond-reinforced and toughened graphene oxide composite film, characterized in that: The preparation method is implemented by the following steps: SS1. Prepare a monolayer graphene oxide (GO) aqueous dispersion to ensure that the GO nanosheet monolayer rate is not less than 99.5%, the average radial size is 20–30 μm, and the GO concentration is controlled at 0.8–1.2 mg / mL to provide a nanosheet base material with uniform dispersion; SS2. Use a balance to weigh 100–400 mg of 65–75 wt% sulfosuccinic acid (SSA) and add it dropwise to the aqueous dispersion of graphene oxide (GO). The mass ratio of GO to SSA is controlled at 1:5 to 1:
20. Stir the mixed solution for 5–8 hours to fully mix SSA and GO to obtain a mixed solution of GO and SSA. SS3. Using water bath ultrasound, the mixed solution of GO and SSA prepared in step SS2 was placed in an ultrasonic water bath with a power of 90–110 W for ultrasonic dispersion for 5–10 min. The ultrasonic temperature was controlled to be no higher than 25°C to fully disperse the GO nanosheets and ensure the formation of a uniform nanoscale suspension. SS4. The mixed solution of GO and SSA after ultrasonic dispersion was vacuum filtered through a water-based microporous filter membrane with a pore size of 0.4–0.5 μm, and the vacuum degree of the filtration was not less than 0.08 MPa, so as to induce GO and SSA to self-assemble into a thin film with a micro-nano multi-level layered structure until a preliminary self-assembled film was formed; SS5. After all the water is drained, continue to drop 0.5–1 mL of 4–6 mol / L hydrochloric acid into the film preliminarily self-assembled on the water-based microporous filter membrane in step SS4, and continue vacuum filtration until the acidified liquid is completely drained to obtain the acidified self-assembled film, and ensure that the hydroxyl groups on the surface of the GO nanosheets are fully exposed and can participate in subsequent chemical reactions; SS6. The acidified self-assembled film obtained in step SS5 is placed in a vacuum drying oven for heat treatment for 1-3 hours, and the temperature is adjusted to 70-90 °C and the pressure is adjusted to 0.8-1.2 atmospheres, so that GO and SSA undergo a covalent cross-linking reaction, and a COC covalent bond is formed by the esterification reaction of the SSA carboxyl group and the GO hydroxyl group to construct an interlayer cross-linking network with high bonding strength, and finally a covalently reinforced and toughened GO-SSA graphene oxide composite film is obtained; SS7. Regulate the mass of SSA weighed in step SS2, blend it with the GO aqueous solution of the same content, repeat steps SS3 to SS6, and obtain a series of GO-SSA graphene oxide composite membranes with different SSA contents and different mechanical properties and photothermal properties, and select the covalently bond-reinforced and toughened graphene oxide composite membranes with the best mechanical strength and toughness, and ensure that the thickness of the composite membrane with the best performance is controlled in the range of 3-5 μm, the tensile strength reaches 400-420 MPa, and the toughness reaches 10-12 MJ / m 3 , the water evaporation rate reaches 2.0 kg·m -2 ·h -1 above.
2. The method for preparing a covalent bond-reinforced and toughened graphene oxide composite film according to claim 1, characterized in that: In the above step SS1, the preparation process of the GO aqueous dispersion includes: dispersing graphite oxide powder in deionized water at a concentration of 0.8-1.2 mg / mL, using a probe-type ultrasonic device with a power of 400-600 W for ultrasonic stripping for 60-90 minutes, using an ice water bath to control the temperature not to exceed 15°C during the ultrasonic process, and then centrifuging at a speed of 4000-6000 rpm for 10-20 minutes, collecting the supernatant to obtain a GO aqueous dispersion with a monolayer rate of not less than 99.5%.
3. The method for preparing a covalent bond-reinforced and toughened graphene oxide composite film according to claim 1, characterized in that: In the above step SS2, the mixing process of GO and SSA further includes: using a magnetic stirrer during the stirring process, controlling the rotation speed to 300-500 rpm, maintaining the stirring temperature at 20-25°C, sampling every 2 hours to test the dispersion stability of the mixed solution by dynamic light scattering method to ensure the dispersion uniformity of the GO nanosheets, until the measured particle size distribution curve remains stable.
4. The method for preparing a covalent bond-reinforced and toughened graphene oxide composite film according to claim 1, characterized in that: In the above step SS3, the temperature range of the ultrasonic water bath is controlled at 20-25 °C, and the ultrasonic process adopts intermittent ultrasonic method, that is, it works for 2 minutes and then pauses for 1 minute, and the cycle is repeated 3-5 times. At the same time, a thermometer is used to monitor the solution temperature in real time. When the temperature exceeds 25 °C, the ultrasonic treatment is stopped immediately, and the treatment is continued when the temperature drops below 20 °C, so as to further reduce the probability of particle sedimentation and enhance the dispersion effect of the mixed solution, thereby improving the microstructure uniformity and film formation quality of the subsequent film layer.
5. The method for preparing a covalent bond-reinforced and toughened graphene oxide composite film according to claim 1, characterized in that: In the above step SS4, the method of inducing self-assembly film formation by vacuum filtration method comprises at least the following sub-steps: SS41. Solution pretreatment The mixed solution of GO and SSA obtained by ultrasonic dispersion in step SS3 was allowed to stand for 2–5 min to ensure the uniformity of the solution and avoid the uniform film formation effect caused by particle aggregation or sedimentation; SS42. Initial filtration operation Without turning on the vacuum pump, add the static mixed solution of GO and SSA into the vacuum filtration device to ensure that the mixed solution evenly covers the surface of the filter membrane; SS43. Start vacuum filtration Keep the mixed solution of GO and SSA in the vacuum filtration device for 2–5 min to ensure that GO After the SSA molecules are fully in contact with the filter membrane, gradually turn on the vacuum pump for vacuum filtration, control the vacuum degree between 0.08-0.10 MPa, and ensure that the filtration speed is slow and uniform to avoid defects or damage on the membrane surface due to liquid flow impact; SS44. Micro-control of membrane layers During the filtration process, GO nanosheets in the mixed solution of GO and SSA gradually deposit on the filter membrane to form a layered microstructure, while SSA small molecules are distributed between the GO nanosheet layers and deposited together on the filter membrane. By adjusting the filtrate discharge rate in real time, the deposition rate and distribution of GO and SSA on the filter membrane surface are optimized to ensure that the final membrane has a good micro-nano multi-level layered structure. SS45. Complete filtration and drying The filtration operation continues until the water is completely drained, and until a uniform and dense graphene oxide composite membrane mixed with SSA is formed on the surface of the filter membrane. After stopping the vacuum pump, the filter membrane is taken out and placed in ventilation conditions for natural air drying or in a dry environment at a temperature of 25-35°C for 30-60 minutes to remove residual moisture and avoid high temperature causing unstable membrane morphology or loose structure.
6. The method for preparing a covalent bond-reinforced and toughened graphene oxide composite film according to claim 1, characterized in that: In the above step SS5, hydrochloric acid is added gradually, and the amount of each addition is controlled at 20-30% of the total amount to ensure that the acid solution is evenly distributed on the surface of the film, and vacuum filtration is performed after each addition to ensure that the acidification process is uniform and sufficient to avoid local insufficient acidification or over-acidification that affects the exposure effect of the hydroxyl groups of the GO nanosheets; and during the acidification process, 0.5-1 wt% ethanol or isopropanol is added to the hydrochloric acid solution as an auxiliary agent to improve the acidification efficiency and slow down the shrinkage of the membrane structure.
7. The method for preparing a covalent bond-reinforced and toughened graphene oxide composite film according to claim 1, characterized in that: In the above step SS6, the heat treatment cross-linking process also includes: controlling the pressure of the vacuum drying oven at 0.8-1.2 atmospheres, and increasing the temperature gradient during the heating process, so that the initial temperature is 50-60 ° C, and gradually increases to 70-90 ° C. After the temperature reaches 70-90 ° C, it is kept at a constant temperature for 2 hours, and then naturally cooled to room temperature at a cooling rate of 1 ° C / min. The entire heat treatment process is carried out under nitrogen protection, and the nitrogen flow rate is controlled at 100-150 mL / min.
8. The method for preparing a covalent bond-reinforced and toughened graphene oxide composite film according to claim 1, characterized in that: In the above step SS7, SSA is modified by adding polyhydroxy compounds or amino compounds as functional group modifiers, so that it forms a more stable covalent cross-linked network with GO nanosheets during acidification and heat treatment, and by optimizing the mass ratio of GO to SSA to 1:10 to 1:25, the thickness and interlayer structure of the film layer are systematically regulated to further improve the photothermal conversion efficiency of the composite film at an intensity of 1 sun.
9. A covalent bond-reinforced and toughened graphene oxide composite film, characterized in that: The preparation of the graphene oxide composite film is based on the method for preparing a covalently bond-reinforced and toughened graphene oxide composite film according to any one of claims 1 to 8.
10. Use of the covalent bond reinforced and toughened graphene oxide composite film according to claim 9 as a substrate material in a solar water evaporation device.
Citation Information
Patent Citations
Preparation method of polyvinyl alcohol / graphite-phase carbon nitride pervaporation hybrid membrane
CN106268332A
Preparation method of pi bond conjugated high-toughness integrated high-conductivity bionic layered graphene composite material
CN106430159A
Preparation method of ultrahigh-strength high-conductive graphene composite thin film with orderly-crosslinked Pi bonds and covalent bonds
CN108516538A
Graphene modification method and application of graphene modification method in lithium battery composite material
CN108878843A
Transparent Gas Barrier Composite Film And Its Preparation Method
US20160046773A1
Cited By
Composite separation membrane as well as preparation method and application thereof
CN120115023A